SYSTEMATIC LITERATURE REVIEW: GENETIC VARIATIONS OF CYP2C9 AS PREDICTORS OF EFFICACY AND SAFETY OF PHENYTOIN THERAPY IN PATIENTS WITH SEIZURE DISORDERS - Megantari, Findari; Purwanto, Djoko Agus; Purnama, Putra Adi; Octaviana, Lenny; Shaleha, Imamatus (HEARTY, 2026)
Background: Phenytoin is an essential anticonvulsant with substantial individual response variability due to CYP2C9 genetic polymorphisms. Objective: To analyze the role of CYP2C9 genetic variations as predictors of phenytoin therapy efficacy and safety in patients with seizure disorders. Methods: A systematic literature review was conducted through comprehensive searches in PubMed, Scopus, Science Direct, and Google Scholar databases using keywords "CYP2C9 polymorphism", "phenytoin", and "epilepsy". Articles published between 2020-2024 were evaluated using structured inclusion and exclusion criteria, with quality assessment using the Newcastle-Ottawa Scale. Results: Ten high-quality articles were analyzed, identifying that CYP2C92, CYP2C93, and CYP2C911 polymorphisms induce enzymatic activity reduction up to 62%, correlating with phenytoin plasma concentration accumulation, increased pharmacological resistance risk (OR 0.11), and elevated severe adverse reaction incidence (OR 12.45). The prevalence of intermediate and poor metabolizer phenotypes reaches 17.8% globally with significant interethnic variation. Conclusion: CYP2C9 genetic variations are significant predictors of phenytoin therapy clinical outcomes, supporting pre-therapy genotyping implementation for anticonvulsant regimen personalization and therapeutic safety optimization.